Involvement of the University Community in Catalonia’s Pro-Independence Political Process - Duart, Josep; Sánchez-Gelabert, Albert; Vilalta, Josep (International Higher Education, 2020)
This article analyses the effects of the pro-independence protests in Catalonia (2017–2019) on Catalan universities and their students. The demonstrations had a moderate impact on the Catalan university system. Large numbers of students took part in the protests. Some universities offered students the chance to pass courses with a single final examination, since they had missed some classes.